Pengaruh Perputaran Modal Kerja dan Perputaran Piutang Terhadap Profitabilitas pada PT. Indofood CBP Sukses Makmur Tbk yang Terdaftar di Bei Periode 2019-2023 - Diva Ariska Ananda; Anwar Ramli; Andika Mustika Amin; Nurman Nurman; Annisa Paramaswary Aslam (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of working capital turnover and accounts receivable turnover on profitability at PT Indofood CBP Sukses Makmur Tbk Listed on the IDX 2019-2023 Period by looking at the performance of financial statements. This study uses descriptive research design with quantitative methods. The research was conducted on annual financial data conducted at PT Indofood CBP Sukses Makmur Tbk which is listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Analysis of the effect carried out by testing three variables, namely working capital turnover and accounts receivable turnover as dependent variables and profitability as an independent variable. The results showed three hypotheses with one accepted hypothesis and two rejected hypotheses. Thus, it can be concluded that in this study only accounts receivable turnover has a significant effect on profitability while working capital turnover has no effect on profitability on the object of study, namely PT Indofood CBP Sukses Makmur Tbk.